Spatial And Temporal Analysis Of Sea Surface Temperature Variability And Chlorophyll-A Over Two Decades In North Sulawesi Waters - Buana, Muhammad Candra; Patty, Wilhelmina; Mantiri, Rose O. S. E.; Budiman, Johnny; Rimper, Joice R.T.S.L.; Rangan, Jety K.; Sumilat, Deiske Adeliene (Sam Ratulangi University, 2024)
Sulawesi waters are directly affected by the dynamics that occur in the Pacific Ocean. The ENSO phenomenon that occurs in the Pacific Ocean can also be felt in the waters of the Sulawesi Sea. The dynamics of oceanographic parameters can cause climate change. The extreme impact of climate change is mainly the occurrence of rising temperatures and seasonal shifts. The purpose of this study is to analyze the variability of spatial and temporal anomalous distribution of sea surface temperature and chlorophyll-a. This study used monthly AQUA Modis image data, conducted by analyzing the spatial and temporal distribution of sea surface temperatures during the two decades of the period 2003 - 2022. This analysis is based on abnormal values obtained from subtracting parameter values from historical values (the average value of all data). The results of spatial variability analysis of sea surface temperature and chlorophyll –show anomalous variations occur in the western and transitional season periods I, while in the eastern season and transition II positive anomalous values dominate the eastern waters negative anomalies dominate the western waters opposite to chlorophyll – a. This study showed that there was an increase in sea surface temperature slope by 0.000840C / year while in chlorophyll - a there was a decrease in slope by 0.00072mg / m3 / year. Keywords: Spatial, Temporal, SPL, Chlorophyll – a, Climate Change. Abstrak Perairan Sulawesi mendapatkan pengaruh secara langsung dari dinamika yang terjadi di Samudera Pasifik. Fenomena ENSO yang terjadi di Samudera Pasifik juga dapat dirasakan dampaknya di perairan Laut Sulawesi. Dinamika parameter oseanografi dapat menyebabkan terjadinya perubahan iklim. Dampak ekstrem dari perubahan iklim terutama adalah terjadinya kenaikan temperatur serta pergeseran musim. Tujuan penelitian ini Menganalisis Variabilitas distribusi anomali spasial dan temporal dari suhu permukaan laut dan klorofil – a, Penelitian ini menggunakan data citra AQUA Modis bulanan, dilakukan dengan menganalisis sebaran spasial dan temporal suhu permukaan laut selama dua dekade periode 2003 - 2022. Analisa ini didasarkan pada nilai anomali yang didapat dari pengurangan nilai parameter dengan nilai historis (rerata nilai seluruh data). Hasil analisis variabilitas spasial suhu permukaan laut dan klorofil – a menunjukan variasi anomali terjadi pada periode musim barat dan peralihan I , sedangkan pada musim timur dan peralihan II nilai anomali positif mendominasi perairan sebelah timur anomali negatif mendominasi perairan sebelah barat sebaliknya dengan klorofil – a. Penelitian ini menunjukan bahwa terjadi peningkatan slope suhu permukaan laut sebesar 0,000840C/ tahun sedangkan pada klorofil - a terjadi penurunan slope sebesar 0,00072mg/m3/tahun. Kata kunci: Spasial, Temporal, SPL, Klorofil – a, Perubahan Iklim.